Harnessing extracellular vesicles to tame inflammation: a new strategy for atherosclerosis therapy - Li, Jiawei; Wen, Tianliang; Li, Xiaoran; Cheng, Ruoyao; Shen, Junyi; Wang, Xin; Guo, Zhaoqi; Teng, Zhengjie; Yi, Lin; Zhang, Fan (Frontiers in Immunology, 2025)
Atherosclerosis (AS) is a chronic inflammatory disease driven by immune dysregulation and vascular inflammation. Extracellular vesicles (EVs) play pivotal roles in intercellular communication, modulating immune responses and inflammatory cascades during AS progression. EVs derived from endothelial cells, macrophages, vascular smooth muscle cells, and platelets transport bioactive molecules (e.g., miRNAs, cytokines) that regulate endothelial dysfunction, macrophage polarization, and plaque instability. Pro-inflammatory EVs exacerbate oxidative stress, foam cell formation, and neutrophil extracellular trap (NET) release, while anti-inflammatory EVs from mesenchymal stem cells or engineered sources attenuate disease by promoting M2 macrophage polarization and suppressing NF-κB signaling. This review highlights the dual roles of EVs in AS immunopathology and their therapeutic potential as biomarkers or nanocarriers for targeted anti-inflammatory interventions. Understanding EV-mediated immune crosstalk may unveil novel strategies for atherosclerosis management.